2019
DOI: 10.1108/jkm-11-2017-0554
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of knowledge sourcing on employee innovation: the moderating effect of information transparency

Abstract: Purpose Innovation is the combination of idea generation and idea implementation. Sourcing relevant and credible external knowledge is critical for individuals to generate new feasible ideas and reduce the uncertainty of implementation. The purpose of this study is to investigate the effects of knowledge sourcing on employee’s innovations behavior. Design/methodology/approach The data were collected by paper-based survey in four Chinese companies’ R&D departments and consisted of 569 valid responses. Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 83 publications
5
60
0
2
Order By: Relevance
“…This means that the more positive explicit knowledge sharing is carried out by the teacher, the more conducive the teacher innovation capability of the individual teacher of the school education institution will be. This finding is in line with previous research on business organizations, namely Perez-Luno et al (2018), Terhorst et al (2018), Boadu et al (2018), Che et al (2019). In contrast to explicit knowledge sharing, tacit knowledge sharing had no significant effect on teacher innovation capability (hypothesis 2 was rejected), except through mediating organizational learning.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…This means that the more positive explicit knowledge sharing is carried out by the teacher, the more conducive the teacher innovation capability of the individual teacher of the school education institution will be. This finding is in line with previous research on business organizations, namely Perez-Luno et al (2018), Terhorst et al (2018), Boadu et al (2018), Che et al (2019). In contrast to explicit knowledge sharing, tacit knowledge sharing had no significant effect on teacher innovation capability (hypothesis 2 was rejected), except through mediating organizational learning.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Leaders who become role models can encourage employees to innovate to become like their leaders, one of them by presenting the results of thought or innovation to other employees, and I want to convince other employees that ideas or innovations are acceptable and supportive pliable the idea. This is in line with research conducted by (Che et al, 2019) which said that transparency will increase employee motivation in work, one of which is transparency related to the rewards system. Highly motivated employees will bring up innovative work behaviors, it is conveyed by (Devloo et al, 2015;Saether, 2019) who says that motivation can improve innovative work behavior.…”
Section: The Relationship Between Authentic Leadership and Psychological Capital On Innovative Work Behaviorsupporting
confidence: 89%
“…For example, Tang () demonstrated that external diversified knowledge increased R&D employees' creativity through their degree centrality of team knowledge network, and the characteristics of knowledge content moderated the contribution of external diversified knowledge and R&D employee creativity. Che, Wu, Wang, and Yang () also find that knowledge sourcing significantly influences employees' innovation behaviour and the effect of knowledge sourcing depends on information transparency. However, no study has analysed the impact of the interaction of internal and external knowledge searching on employee creativity from the domain perspective or identified domain differences in the use of knowledge searching sources.…”
Section: Discussionmentioning
confidence: 95%